Future anxiety and its relationship to level of aspiration among physical education students - Kenioua, Mouloud; Boumesjed, Abd El-kadder (Revue Sciences et Pratiques des Activités Physiques Sportives et Artistiques, 2018)
The purpose of this study was to know the level of future anxiety, level of aspiration among physical education students and to reach of finding the relationship between future anxiety and level of aspiration. The sample consisted of male physical education students (players (N =63) from Institute of Physical Education and Sport University of Ouargla. Future anxiety scale and level of aspiration were used to collection data. Descriptive statistics, and person’s correlation analysis were used to calculate data. The results indicated that there was low future anxiety among physical education students and high level of aspiration among physical education students. No correlation relationship between future anxiety and level of aspiration. The most important thing researchers recommend is developing sport programs that reduce the level of anxiety and enhance the level of aspiration in all sports (Sports University, amateur, professional).
Keywords: future anxiety; level of aspiration; physical education students